2021
DOI: 10.1001/jamanetworkopen.2021.34908
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Impaired Kidney Function Among Adolescent Patients Hospitalized With Anorexia Nervosa

Abstract: Key Points Question What is the incidence of impaired kidney function in adolescents with anorexia nervosa, and how does it correlate with body mass index and physiologic parameters of anorexia nervosa severity? Findings In this case-control study of 395 adolescent patients with recent diagnosis of anorexia nervosa, impaired kidney function was found in 36.8%. Minimal heart rate and free triiodothyronine levels showed correlation with eGFR but not with admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As previously reported (Gurevich et al, 2021; Stheneur et al, 2019), eGFR was low in a large proportion of our adolescent and young adult patients with restrictive EDs hospitalized for nutritional support. This proportion, while high, is likely an underrepresentation of the true extent of kidney dysfunction in this population since serum creatinine concentrations depend on muscle mass, which is particularly low in malnourished individuals.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As previously reported (Gurevich et al, 2021; Stheneur et al, 2019), eGFR was low in a large proportion of our adolescent and young adult patients with restrictive EDs hospitalized for nutritional support. This proportion, while high, is likely an underrepresentation of the true extent of kidney dysfunction in this population since serum creatinine concentrations depend on muscle mass, which is particularly low in malnourished individuals.…”
Section: Discussionsupporting
confidence: 84%
“…Thirty‐three percent of patients ( n = 23) demonstrated a serum bicarbonate concentration above the normal range (i.e., above 29 mEq/L) at some point in their admission. Urine pH did not increase during these episodes, however; urine pH values were 7 (Casiero & Frishman, 2006; Gurevich et al, 2021) when serum bicarbonate concentrations were increased. A linear mixed model demonstrated that net fluid balance, hospital day, and the interaction between hospital day and net fluid balance were independent predictors of serum bicarbonate concentration during hospitalization (Table 2).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Reduced hepatic function could have additional consequences for skeletal muscle size and function given the liver is a significant moderator of whole body and amino acid metabolism, and thus, important for muscle metabolic health. Altered renal function has also been noted in patients with AN (Gurevich et al, 2021). Finally, immune function, appears modified in patients with AN.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in kidney function and electrolyte disturbances are frequently seen in patients with ED, including acute kidney injury (AKI) and chronic kidney disease (CKD) [ 4 ], most often related to chronic hypokalemia (serum potassium < 3.5 mEq/L) and volume depletion [ 5 ]. AKI is a “heterogeneous group of conditions characterized by a sudden decrease in glomerular filtration rate (GFR) followed by an increase in serum creatinine concentration or oliguria [low urine output]” which can lead to serious complications including volume overload and electrolyte abnormalities and can progress to CKD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%